2022
DOI: 10.1038/s41598-022-17405-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between amorphous calcium-phosphate ratios in circulating calciprotein particles and prognostic biomarkers in hemodialysis patients

Abstract: Calciprotein particles (CPPs) are circulating colloidal mineral-protein complexes containing crystalline and/or non-crystalline (amorphous) calcium-phosphate (CaPi). Serum CPP levels correlate with vascular stiffness and calcification in patients with chronic kidney disease (CKD). In vitro studies showed that CPPs containing crystalline CaPi were more arteriosclerogenic and inflammogenic than CPPs without containing crystalline CaPi. Thus, we hypothesized that not only the quantity but also the quality of CPPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Multivariate analysis showed a stronger effect of phosphorus on plasma CPP (CPP-II) and serum CPP (CPP-I + II) than calcium, and the relationship between CPP and phosphorus levels differed among HD groups. Plasma CPP (CPP-II) levels, which have pathogenic activity by inducing calcification and immune responses [ 14 ], increased more gradually with increasing phosphorus levels in the extended-hours HD group than in the conventional HD group. These results suggest that phosphorus-induced vascular calcification is less likely to occur in patients on extended-hours HD, which may partially explain their favourable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate analysis showed a stronger effect of phosphorus on plasma CPP (CPP-II) and serum CPP (CPP-I + II) than calcium, and the relationship between CPP and phosphorus levels differed among HD groups. Plasma CPP (CPP-II) levels, which have pathogenic activity by inducing calcification and immune responses [ 14 ], increased more gradually with increasing phosphorus levels in the extended-hours HD group than in the conventional HD group. These results suggest that phosphorus-induced vascular calcification is less likely to occur in patients on extended-hours HD, which may partially explain their favourable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CPP levels in serum samples represent total CPP levels (CPP-I and CPP-II) because blood coagulation accelerates the amorphous-to-crystalline phase transition of CaPi in CPP-I (Fig. 1 ) [ 14 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…CPPs, as already mentioned, can be distinguished in two sequential forms: primary CPPs, small complexes of amorphous calcium phosphate, and secondary CPPs, containing a needle-shaped crystallized complex of calcium phosphate [ 135 ]. CPPs’ serum levels increase CKD progression [ 136 ]. A recently developed in vitro assay can identify the propensity of VC formation and overall calcification by measuring the semi maximal conversion time (T50, in minutes) from primary to secondary CPPs when given additional calcium and phosphate [ 137 ].…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Considering this, numerous attempts have been undertaken in the development of ACP composite materials using macromolecules such as osteopontin, osteocalcin, dentin matrix protein, bone sialoprotein, dentin phosphoprotein, matrix extracellular protein, connexin 43, casein phospho-peptide, α 2 HS-glycoproteins, fibrin, and albumin (Reynolds, 1998;Makowski and Ramsby, 2001;Gajjeraman et al, 2007;Yang et al, 2010;Yarbrough et al, 2010;Syed-Picard et al, 2013;Padovano et al, 2015;Zhao et al, 2018;Iline-Vul et al, 2020;Erceg and Dutour Sikirić, 2022;Nakamura et al, 2022;Indurkar et al, 2023a). However, Becher et al have identified that many biological ubiquitous small organic molecules can inhibit the conversion of ACP to HAp at their respective tissue concentration (Becker, 1977).…”
Section: Introductionmentioning
confidence: 99%